2018
DOI: 10.1111/pan.13418
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes and management in midface advancement surgery: a multicenter observational descriptive study from the Pediatric Craniofacial Collaborative Group

Abstract: Monobloc procedures were associated with greater transfusion and longer ICU and hospital length of stay. Perioperative complications were more prevalent in the Monobloc group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…When we evaluated the intraoperative fluid management of these patients undergoing Monobloc distraction; we observed that no colloid was given, yet a high amount of blood was transfused (52%; 40 ml.kg −1 , 35%; 60 ml.kg −1 and 17%; 80 ml.kg −1 ). More restrictive transfusion practices have been recommended in this population to reduce complications and improve patient safety 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we evaluated the intraoperative fluid management of these patients undergoing Monobloc distraction; we observed that no colloid was given, yet a high amount of blood was transfused (52%; 40 ml.kg −1 , 35%; 60 ml.kg −1 and 17%; 80 ml.kg −1 ). More restrictive transfusion practices have been recommended in this population to reduce complications and improve patient safety 29 …”
Section: Discussionmentioning
confidence: 99%
“…More restrictive transfusion practices have been recommended in this population to reduce complications and improve patient safety. 29…”
Section: Figurementioning
confidence: 99%
“…However, clinician experience supported by several retrospective studies identified some physical risk factors for a difficult airway in neonates and infants: micro-, retro-, or prognathia, limited mouth opening, facial asymmetry, fixed cervical spine, labio-palatine cleft, and oral or neck mass 10–12 . These physical features commonly exist in neonates and infants with syndromes associated with anticipated difficult airway management such as the Pierre Robin, Crouzon, and Treacher-Collins syndromes 11,13 . However, there are no studies prospectively evaluating the role of physical features in predicting difficult airway management (mask ventilation or tracheal intubation) in neonates and infants with an apparently normal airway.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] These physical features commonly exist in neonates and infants with syndromes associated with anticipated difficult airway management such as the Pierre Robin, Crouzon, and Treacher-Collins syndromes. 11,13 However, there are no studies prospectively evaluating the role of physical features in predicting difficult airway management (mask ventilation or tracheal intubation) in neonates and infants with an apparently normal airway. While several adult based studies have suggested simple summations or weighted risk scores for predicting 'unanticipated' difficult tracheal intubation based on physical measures (e.g.…”
Section: Development Of Recommendationsmentioning
confidence: 99%
“…To our knowledge, there is currently no large, published case series of perioperative airway complications and management in patients with Crouzon and Pfeiffer syndromes. Most of the current published literature is limited to single case reports relating to anesthetic management 6–8 or larger series focusing on craniofacial surgical complications 9,10 …”
Section: Introductionmentioning
confidence: 99%